Comparison of BMI, waist circumference, and waist‐to‐height ratio for identification of subclinical cardiovascular risk in pediatric kidney transplant recipients. (7th October 2018) - Sgambat, Kristen; Clauss, Sarah; Moudgil, Asha
Abstract: Background: Kidney transplant recipients are at high risk for CV morbidity. However, the measure of obesity that best predicts CV risk has not been established. Objective: A prospective, controlled study was conducted to compare the ability of BMI, WC, and WHr to identify CV risk in pediatric kidney transplant recipients. Methods: Transplant recipients, aged 3‐20 years, had echocardiogram, CIMT, BMI, WC, WHr, blood pressure, lipids, and leptin measured. Receiver operating characteristic analysis was used to compare the ability of BMI, WC, and WHr to detect a composite adverse CV outcome. Presence of the composite outcome was defined by ≥3 of the following five criteria: (a) LVH, (b) high CIMT, (c) impaired myocardial strain, (d) dyslipidemia, and/or (e) hypertension. Multivariate analysis was conducted by generalized estimating equation regression. Results: We analyzed 108 visits of 42 transplant recipients. Prevalence of obesity by WHr (43.5%) was higher than BMI (24.1%) and WC (12.0%). Proportion of WHr‐obese who met criteria for the adverse CV outcome was higher (62.2%) than BMI (34.6%) and WC‐obese (33.3%). Leptin levels were higher in children with obesity. Area under the ROC curve for WHr‐obese (0.77) was higher compared to BMI (0.47) and WC (0.48) to detect the CV outcome, P  = 0.0006. WHr‐obesity was associated with 5.72 increased odds of having the adverse CV outcome, P  = 0.0001, while BMI and WC were not significant. Conclusion: WHr is more sensitive than BMI or WC to detect subclinical CV risk and should be included in screening of pediatric kidney transplant recipients.